Anti-cancer therapeutic potential of quinazoline based small molecules via global upregulation of miRNAs - Nahar, Smita; Bose, Debojit; Panja, Sumit Kumar; Saha, Satyen; Maiti, Souvik (Chemical Communications, 2014)
Three quinazoline based small molecules showed global upregulation of miRNA expression with a selective enrichment of tumor suppressor miRNAs. The target genes of the upregulated miRNAs were predicted to be enriched for apoptotic pathways. Apoptotic induction following treatment with quinazoline compounds was confirmed by in cellulo studies. Thus, these small molecules having the core structural moiety (2,4-diphenyl-quinazoline) can be used as scaffolds to design activators of miRNA expression paving the way for novel anti-cancer drugs.

Beta, gamma-Bis-substituted PNA with configurational and conformational switch: preferred binding to cDNA/RNA and cell-uptake studies - Bose, Tanaya; Banerjee, Anjan; Nahar, Smita; Maiti, Souvik; Kumar, Vaijayanti A. (Chemical Communications, 2015)
(S,S)- and (R,R)-beta,gamma-Bis-substituted PNAs were synthesized from the C-2 symmetric vicinal diamine system embedded in 1,4 dihydroxybutane and 1,4-dimethoxybutane scaffolds. (R,R)-beta,gamma-Bis-methoxymethyl-PNA derived from D-tartaric acid was found to be in the right configuration and conformation to be an excellent mimic of PNA, endowed with superior ability to enter into cells.

Cyclic cationic peptides containing sugar amino acids selectively distinguishes and inhibits maturation of pre-mirnas of the same family - Nahar, Smita; Bose, Debojit; Pal, Sudip; Chakraborty, Tushar Kanti; Maiti, Souvik (Nucleic Acid Therapeutics, 2015)
The discovery of microRNAs (miRNAs) has added a new dimension to the gene regulatory networks, making aberrantly expressed miRNAs as therapeutically important targets. Small molecules that can selectively target and modulate miRNA levels can thus serve as lead structures. Cationic cyclic peptides containing sugar amino acids represent a new class of small molecules that can target miRNA selectively. Upon treatment of these small molecules in breast cancer cell line, we profiled 96 therapeutically important miRNAs associated with cancer and observed that these peptides can selectively target paralogous miRNAs of the same seed family. This selective inhibition is of prime significance in cases when miRNAs of the same family have tissue-specific expression and perform different functions. During these conditions, targeting an entire miRNA family could lead to undesired adverse effects. The selective targeting is attributable to the difference in the three-dimensional structures of precursor miRNAs. Hence, the core structure of these peptides can be used as a scaffold for designing more potent inhibitors of miRNA maturation and hence function.

Nonconventional chemical inhibitors of microRNA: therapeutic scope - Jayaraj, Gopal Gunanathan; Nahar, Smita; Maiti, Souvik (Chemical Communications, 2015)
MicroRNAs (miRNAs) are a class of genomically encoded small RNA molecules (similar to 22nts in length), which regulate gene expression post transcriptionally. The term microRNA or miRNA was coined in 2001, and research in the past decade has shed light on their widespread occurrence, evolutionary conservation and tissue specific functions. It is estimated that they modulate the gene expression of approximately 60% of the mammalian genes by regulating the levels of target mRNAs to which they can bind on the basis of sequence complementarities. miRNAs are produced in a well coordinated series of steps from being transcribed in the nucleus to exerting their function in the cytoplasm. miRNAs are now implicated in diverse biological phenomena ranging from development to stress response which makes miRNAs one of the central regulatory molecules which modulate information flow along the central dogma of gene expression. More importantly, like any regulatory molecule, deregulation of miRNAs is causally associated with several diseases (mainly cancer) and is directly involved in a variety of pathophysiologies owing to their aberrant expression. Thus, modulation of miRNA levels is of prime therapeutic importance. Conventional methods of miRNA knockdown using chemically modified antisense-oligonucleotides have been explored extensively but face the challenges of modes of delivery, biostability and biodistribution. This calls for the development of more alternative and non-conventional methods to target miRNA. Small molecules targeting RNA chemical and structural space provide one such timely opportunity. In this article we first provide a brief overview of miRNA biogenesis and its disease associations. We then summarize the major developments in conventional oligonucleotide based approaches to miRNA knockdown and its status. We then focus on the more non-conventional methods like oligonucleotide enzymes and small molecules and provide an outlook on the future of such methods.

Potent inhibition of miR-27a by neomycin-bisbenzimidazole conjugates - Nahar, Smita; Ranjan, Nihar; Ray, Arjun; Arya, Dev P.; Maiti, Souvik (Chemical Science, 2015)
miRNAs are important components of regulatory networks that control gene expression and have implications in various diseases including cancer. Targeting oncogenic miRNAs with small molecules is currently being explored to develop cancer therapeutics. Here, we report the development of dual binding neomycin-bisbenzimidazole conjugates that target oncogenic miR-27a with high affinity (K-a = 1.2 to 7.4 x 10(8) M-1). These conjugates bring significant reduction (similar to 65% at 5 mu M) in mature miRNA levels and penetrate easily in the cells where they localise both in the cytoplasm and the nucleus. Cell cycle analysis showed significant increase in the G0/G1 phase (similar to 15%) and decrease in the S phase (similar to 7%) upon treatment with neomycin-bisbenzimidazole conjugates, suggesting inhibition of cell proliferation. Using the conjugation approach, we show that moderately binding ligands can be covalently combined into high affinity binders. This study also highlights the role of linker optimization in designing high affinity ligands for miR-27a targeting.

Selective inhibition of miR-21 by phage display screened peptide - Bose, Debojit; Nahar, Smita; Rai, Manish Kumar; Ray, Arjun; Chakraborty, Kausik; Maiti, Souvik (Nucleic Acids Research, 2015)
miRNAs are nodal regulators of gene expression and deregulation of miRNAs is causally associated with different diseases, including cancer. Modulation of miRNA expression is thus of therapeutic importance. Small molecules are currently being explored for their potential to downregulate miRNAs. Peptides have shown to have better potency and selectivity toward their targets but their potential in targeting and modulating miRNAs remain unexplored. Herein, using phage display we found a very selective peptide against pre-miR-21. Interestingly, the peptide has the potential to downregulate miR-21, by binding to pre-miR-21 and hindering Dicer processing. It is selective towards miR-21 inside the cell. By antagonising miR-21 function, the peptide is able to increase the expression of its target proteins and thereby increase apoptosis and suppress cell proliferation, invasion and migration. This peptide can further be explored for its anti-cancer activity in vivo and may be even extended to clinical studies.

Inhibition of miR-21 by 3 `/5 `-serinyl-capped 2 `-O-Methyl RNA Interspersed with 2 `-O-(2-Amino-3-Methoxypropyl) uridine units - Nahar, Smita; Kotikam, Venubabu; Kumar, Vaijayanti A.; Maiti, Souvik (Nucleic Acid Therapeutics, 2016)
miRNAs are highly conserved class of small ncRNAs whose involvement in human pathophysiologies is extensively investigated. MiR-21 is a well established oncogenic miRNA whose deregulation plays a significant role in onset and progression of cancer. The need of novel approaches to downregulate miR-21 is rapidly expanding. Potent inhibition of miR-21 is achieved by chemically modified 2-O-methyl RNA oligonucleotide. The serinol capping at 3 and 5ends and the interspersed 2-O-(R-2-amino-3-methoxypropyl) uridine units enhance the nuclease resistance and efficacy of 2-O-methyl RNA for the inhibition of miR-21. This represents a simple and novel modification for developing oligonucleotide-based therapeutics.
Keywords: antagomirs; cancer; microRNA; noncoding RNA; oligonucleotides

Systematic evaluation of biophysical and functional characteristics of selenomethylene-locked nucleic acid-mediated inhibition of miR-21 - Nahar, Smita; Singh, Amrita; Morihiro, Kunihiko; Moai, Yoshihiro; Kodama, Tetsuya; Obika, Satoshi; Maiti, Souvik (Biochemistry, 2016)
miRNAs constitute an important layer of gene regulation mediated by sequence-specific targeting of mRNAs. Aberrant expression of miRNAs contributes to a host of pathological states. Promoting cancer, miR-21 is upregulated in variety of cancers and promotes tumor progresion by suppressing a network of tumor suppressor genes. Here we describe a novel class of bicyclic RNA analogues, selenomethylene-locked nucleic acid (SeLNA), that display high affinity, improved metabolic stability, and increased potency for miR-21 inhibition. The thermal stability (T-m) for duplexes was increased significantly with incorporation of SeLNA monomers as compared to that of the unmodified DNA RNA hybrid. A comprehensive thermodynamic profile obtained by isothermal titration calorimetry revealed a favorable increase in the enthalpy of hybridization for SeLNA containing DNA and target RNA heteroduplexes. SeLNA modifications displayed remarkable binding affinity for miR-21 target RNA with a K-a of <= 1.05 x 10(8) M-1. We also observed enhanced serum stability for SeLNA RNA duplexes with a half-life of <= 36 h. These in vitro results were well correlated with the antisense activity in cancer cells imparting up to similar to 91% inhibition of miR-21. The functional impact of SeLNA modifications on miR-21 inhibition was further gauged by investigating the migration and invasion characterisitics of cancer cells, which were drastically reduced to similar to 49 and similar to 55%, respectively, with SeLNA having four such modifications. Our findings demonstrate SeLNA as a promising candidate for therapeutics for disease associated miRNAs.

G-quadruplex motif at the 3' end of sgRNAs improves CRISPR-Cas9 based genome editing efficiency - Nahar, Smita; Sehgal, Paras; Azhar, Mohammad; Rai, Manish; Singh, Amrita; Sivasubbu, Sridhar; Chakraborty, Debojyoti; Maiti, Souvik (Chemical Communications, 2018)
Originating as a component of prokaryotic adaptive immunity, the type II CRISPR/Cas9 system has been repurposed for targeted genome editing in various organisms. Although Cas9 can bind and cleave DNA efficiently under in vitro conditions, its activity inside a cell can vary dramatically between targets owing to differences between genomic loci and availability of enough Cas9/sgRNA (single guide RNA) complex molecules for cleavage. Most methods to improve CRISPR/Cas9 activity have so far relied on Cas9 protein engineering or base modifications in the sgRNA sequence. Here we demonstrate that a structure based rational design of sgRNAs can enhance the efficiency of Cas9 cleavage in vivo. By appending a naturally forming RNA G-quadruplex motif to the 3′ end of sgRNAs we can improve its stability and target cleavage efficiency in zebrafish embryos without inducing off-target activity, thereby underscoring its value in the design of better and optimized genome editing triggers.